Optimized immunocytochemistry using leukocyte and tissue markers on Romanowsky‐stained slides from dogs and cats. (25th July 2019) - Raskin, Rose E.; Vickers, Julie; Ward, Jennifer G.; Toland, Angus; Torrance, Andrew G.
Abstract: Background: Romanowsky staining is often the initial method used to stain hematologic and cytologic materials. While immunocytochemistry (ICC) is a well‐established method on air‐dried smears, there are rare veterinary reports of ICC involving Romanowsky‐stained slides. Objectives: This study aimed to compare immunoreactivity of unstained vs Romanowsky‐stained specimens, evaluate reactions over time, and assess ICC associations with confirmatory tests of 50 lymphoma cases. Another goal aimed to optimize manual ICC protocols with cellular and tissue immunomarkers to detect CD3ε, CD20, Pax5, MHCII, lysozyme, MUM1, vimentin, cytokeratin, and Melan‐A antigens on Romanowsky‐stained specimens. Materials and methods: Cytologic specimens from cases of lymphoid and nonlymphoid neoplasms were stained with a methanolic Romanowsky method. Additional unstained slides from these cases were used for comparison with the stained materials. Antigen retrieval involved a citrate buffer pH6 or Tris/EDTA pH9 at 95°C for 25 minutes in a decloaking chamber. Immunocytochemistry used known positive and secondary antibody‐only negative cytologic controls. Immunoreactivity of unstained and prestained lymphoma slides was graded by the intensity and percent of stained cells. Signal grading was monitored over time for diagnostic differences. Results: Unstained and Romanowsky‐stained slides had similar membrane/cytoplasm graded reactions, but unstained slides produced stronger signals. Romanowsky‐stained blood films from B‐cell and T‐cell leukemias showed minimal loss of signal when monitored over 20 weeks. Signal differences did not change the diagnosis. There was a significant association between ICC and confirmatory tests. Optimization involved antibody dilution and antigen retrieval methodology for each antibody tested. Conclusions: Immunocytochemistry of Romanowsky‐stained material can be successfully performed using antibodies against CD3ε, CD20, cytokeratin, lysozyme, Melan‐A, MHCII, MUM1, Pax5, and vimentin.